Effectiveness of Structured Teaching Program on Secondary Students’ Knowledge and Perception of Nursing as a Career Choice in Golaghat, Assam - Rituporna Dutta (Indian Journal of Nursing Sciences, 2025)
Background: The nursing profession has evolved significantly, adapting to modern health-care needs. Choosing a career is a complex decision influenced by personal characteristics, societal values, and understanding of the profession. In the case of nursing, many individuals possess limited knowledge about its scope and responsibilities, often relying on misconceptions. Raising awareness and promoting a positive image of nursing can encourage more students to consider it as a viable career path. Raising awareness and creating a more positive image of the nursing profession can encourage further individuals to consider it as a career choice. Materials and Methods: A quantitative, pre-experimental design was used, and the study was conducted in selected schools within the Golaghat district, Assam. Data were collected from a sample of 1015 secondary school students. Data collection tools included a demographic questionnaire, a structured knowledge questionnaire, and a perception scale. Results: The post-test results showed a substantial enhancement in knowledge, with scores rising from a mean of 1.95 (standard deviation [SD] ± 1.92) in the pre-test to 9.56 (SD ± 2.32) post-intervention (P < 0.001). Furthermore, perception scores increased from 26.01 (SD ± 8.90) to 48.17 (SD ± 7.38) after the structured teaching program (P < 0.001). Only 10.64% students had adequate knowledge on nursing as a career choice during the pre-test, which increased to 95.66% during the post-test. Similarly, the percentage of students who perceived nursing as a good career choice was only 12.70% during pre-test, which increased to 88.86% after the intervention. A significant association was linked between knowledge of nursing as a career choice and the occupation of mother, while gender, maternal employment, and family ties to the nursing field were significantly associated with the perception toward nursing as a career choice. Recommendations: More interventional studies can be conducted to educate the public and scholars about the different opportunities within nursing, from leadership positions to advanced clinical specializations.